Viral Infections, an Overview with a Focus on Prevention of Transmission - Cheng, Vincent Chi-Chung (International Encyclopedia of Public Health, 2017)
Viruses are obligatory intracellular pathogens with a simple structure consisting of assembled proteins enclosing the nucleic acid genome with or without a lipid envelope. Despite increasing availability of rapid nucleic acid amplification assays for laboratory diagnosis, effective antivirals, and safe vaccines, the control of most viral infections depends on time-honored surveillance and infection control measures. Moreover most viruses can be readily destroyed by common disinfectants. This article is focused on the epidemiology, diagnosis, and control of common and emerging viral diseases.